Structural engineering of SnS2/Graphene nanocomposite for high-performance K-ion battery anode. (June 2019) - Bin, De-Shan; Duan, Shu-Yi; Lin, Xi-Jie; Liu, Lin; Liu, Yuan; Xu, Yan-Song; Sun, Yong-Gang; Tao, Xian-Sen; Cao, An-Min; Wan, Li-Jun
Abstract: K-ion batteries (KIBs) are drawing increasing research interest as a promising supplement of Li-ion batteries due to the natural abundance of K resource. However, due to the large size of K +, high-capacity anodes are challenged by the structural stability of the active materials which are susceptible to large volumetric deformation after incorporating with a sufficient number of K + . Herein, using SnS2 /graphene as an example, we demonstrated that high-performance KIBs anode could be achieved through collaborative efforts targeting on both the active material and the prepared electrode film. The electrochemically-active species of SnS2 were controlled into small nanoparticles with their size below 5 nm to provide sufficient reactive sites for K + storage. Meanwhile, highly-resilient electrode film based on the prepared SnS2 /graphene nanocomposite was built on aluminum (Al) current collector rather than the widely-used copper foil, forming a strong anode film with high peel strength to endure the potassiation/depotassiation process. In this way, the active species was able to deliver an extraordinary reversible capacity of 610 mAh g −1 with unprecedented high-rate capability (around 290 mAh g −1 at 2A g −1 ) and promising cycling stability. This contribution sheds light on the rational design of high-performance electrode for KIBs and beyond. Graphical abstract: A High-performance potassium-ion battery anode, which was constructed by building the highly-dispersed sub-5nm SnS2 /graphene composite on the lighter and lower-cost Al current collector rather than the widely-used copper foil, could deliver extraordinary capacity (610 mAh g −1 ), unprecedentedly high-rate capability (around 290 mAh g −1 at 2A g −1 ), and promising cycling stability. It envisions new perspectives on the rational design of high-performance electrode for KIBs and beyond.Image 1 Highlights: SnS2 /graphene with high-dispersity sub-5nm SnS2 nanoparticles was synthesized as K-ion battery anode. High-peel-strength electrode was designed based on the lower-cost aluminum current collector. It delivers unprecedentedly high electrochemical performance in K-ion battery. The feasibility of a K-ion full cell based on dual-Al current collector was demonstrated.